Zobaczyć Ojca w Synu w Ewangelii św. Jana - Kuśmirek, Anna (Verbum Vitae, 2009)
The Fourth Gospel lays great emphasis on seeing, on seeing the work of the Father in the work of Jesus, on seeing the Father's glory, and even on seeing the Father himself in the Son. The article explores the verses in which seeing Jesus include seeing God or Father (J 6,62; J 1,18;12,45; 14,9). The Fourth Gospel limits “seeing God” to Jesus alone (1,18; 6,45-46). His vision of God bas unique character because only the Son has seen the Father. The disciples see Jesus, or God as manifested in and through Jesus (14,9). Johannine concept of seeing operates on two different levels. The first is that of physical seeing experienced by those who actually saw Jesus and works he did. The second level is that o f spiritual seeing, or faith. Some who physically saw also went on to see by responding in faith that means seeing involves faith to the revelation of God in Jesus Christ. To see the Father in the Son is to see the Son and so to come to perceive or understand their relationship and their unity.